MENCIPTAKAN PEMBELAJARAN EFEKTIF MELALUI HYPNOTEACHING - Muhammad Anwar HM (EKSPOSE, 2017)
The aim of this paper is to provide the information to educators on hypnoteaching as one of the alternative methods that can be used to create effective learning. The effective learning is the learning that enables learners to learn easy, fun, and can achieve the learning objectives that have been set. Hypnoteaching is the learning methods in delivering the subject matter, the teacher uses the communication techniques are very persuasive and suggestive with the aim that students easily understand the subject matter. Hypnoteaching steps include: 1) intention and motivation within yourself; 2) pacing or equalize the position, gestures, language, and brain waves with others or learners; 3) leading or directing learners; 4) using positive words; giving a compliment; 6) modeling or exemplify through speech and behavior. If teachers apply hypnoteacing in the learning activities, the classroom atmosphere will be more conducive, learners feel important, safe and comfortable so that the goal of learning more easily is achieved